Measurements of the absolute branching fractions and CP asymmetries for D+ -> (KS,LK+)-K-0 (pi(0)) - Çetin, Serkant Ali (AMER PHYSICAL SOC, 2019)
Using e(+)e(-) collision data corresponding to an integrated luminosity of 2.93 fb(-1) taken at a center-of-mass energy of 3.773 GeV with the BESIII detector, we determine the absolute branching fractions B(D+ -> (KSK+)-K-0) = (3.02 +/- 0.09 +/- 0.08) x 10(-3), B(D+ -> (KSK+)-K-0 pi(0)) = (5.07 +/- 0.19 +/- 0.23) x 10(-3), B(D+ -> (KLK+)-K-0) = (3.21 +/- 0.11 +/- 0.11) x 10(-3), and B(D+ -> (KLK+)-K-0 pi(0)) = (5.24 +/- 0.22 +/- 0.22) x 10(-3), where the first and second uncertainties are statistical and systematic, respectively. The branching fraction B(D+ -> (KSK+)-K-0) is consistent with the world average value and the other three branching fractions are measured for the first time. We also measure the CP asymmetries for the four decays and do not find a significant deviation from zero.